2021
DOI: 10.1126/sciadv.abh1448
|View full text |Cite
|
Sign up to set email alerts
|

In vivo rate-determining steps of tau seed accumulation in Alzheimer’s disease

Abstract: Local replication doubles the number of tau aggregate in Alzheimer’s disease only once every 5 years, limiting the overall rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 44 publications
5
77
1
Order By: Relevance
“…Our findings support recent studies that suggest Alzheimer’s disease clinical symptomatology begins when tau aggregates exist in multiple brain regions; that is, inhibiting the initial stochastic sequence(s) that enhance neurodegeneration before propagation is likely to be an effective treatment and not preventing spread [ 32 ].…”
Section: Resultssupporting
confidence: 89%
“…Our findings support recent studies that suggest Alzheimer’s disease clinical symptomatology begins when tau aggregates exist in multiple brain regions; that is, inhibiting the initial stochastic sequence(s) that enhance neurodegeneration before propagation is likely to be an effective treatment and not preventing spread [ 32 ].…”
Section: Resultssupporting
confidence: 89%
“…Thus, solutions that target senescent glia in LOAD will likely help managing or treating symptoms in these other diseases; co-morbid pathologies may also have independent mechanisms inducing glial senescence. Furthermore, data from tau PET studies indicated that tau seeding occurs locally from Braak stages III+ 132 . As this tau propagation is correlated with increased microglial activity 146 , this reinforces the idea of paracrine glial senescence via spreading hp-tau.…”
Section: Discussionmentioning
confidence: 99%
“…Senescent microglia are thus putatively accountable for neuritic plaque formation and indirect NFT formation, critical A, hp-tau, and pro-inflammatory cytokine pathology beyond threshold tolerance, among localized brain regions corresponding to Braak staging, and overall LOAD progression 1,8,61,62,82,83,94,132 . Furthermore, state "B" senescent microglia are predicted to respond to overwhelming A aggregation with an increased type I IFN response 23,[97][98][99] , leading to pro-inflammatory cytokine secretion and Kv1.3 expression exacerbating local inflammation 122,[133][134][135] .…”
Section: Senescent Microglia Are Predicted To Transform Morphology Dr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the proteins follows the dynamics of a modified heterodimer model with local and nonlocal interactions and a coupling parameter between two proteins 20,[27][28][29][30] . Motivated by Meisl et al 31 , we replace exponential growth with logistic growth in both the proteins Aβ and τP. Due to toxic variants of these proteins present in the brain cell, neuronal damage occurs in the brain.…”
Section: Introductionmentioning
confidence: 99%